7n - 3
It is: 25-7n
Un = 25 - 7n
The nth term is 7n-3 and so the next term will be 39
Without further restrictions it can be any of an infinite number of formulae.For example, U{n} = (11n⁴ - 110x³ + 385x² - 518x + 176)/8 which gives the next term as 42.However, if it is an ARITHMETIC SEQUENCE (as I suspect your teacher wants), then the nth term is found:Common difference: (-3) - (-7) = 4→ 0th term is -7 - 4 = -11→ nth term U{n} = 4n - 11
11
1...2....3....43...7...11..157 - 3 = 411 - 7 = 415 - 11 = 4(the start of the nth term is 4n)4 x 1 = 4(but the first term is 3, so...)4 -1 = 3nth term = 4n - 1
7n - 3
It is: 25-7n
Un = 25 - 7n
The nth term is 7n-3 and so the next term will be 39
1 +3 =4 +3+4 =11 +3+4+4 =22 +3+4+4+4 37 +3+4+4+4+4 .... u can c where i am goin here
The nth term is: 3n-7 and so the next number will be 11
The nth term is: 3n-7 and so the next number will be 11
2n+5
Without further restrictions it can be any of an infinite number of formulae.For example, U{n} = (11n⁴ - 110x³ + 385x² - 518x + 176)/8 which gives the next term as 42.However, if it is an ARITHMETIC SEQUENCE (as I suspect your teacher wants), then the nth term is found:Common difference: (-3) - (-7) = 4→ 0th term is -7 - 4 = -11→ nth term U{n} = 4n - 11
If you mean: 3, 4, 5, 6 and 7 then nth term = n+2